FINANCIAL LITERACY: IMPROVING LONG-TERM PERFORMANCE AND INVESTMENT OF UMKM IN CENTRAL JAVA - Gunawan, Ade; Harywibowo, M. Risqi; Salsabilah, Lulu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
UMKM in Central Java plays an important role in the regional economy. Through the Department of Cooperation and Central Java UKM, recorded during 2023 has built 187.000 more UMKM. As for, the total UMKM in Jateng reached 4.2 million. However, many UMKMs are still controlled by weak access to funding, marketing, and financial management. In addition, the literacy rate in Central Java was recorded at 51.69 per cent, while the level of financial inclusion or availability of financial access was registered higher by 85.97 per cent. The study aims to analyse the impact of financial literacy on the performance and long-term investment of UMKM in Central Java. Research data is collected through literature studies. Research results show that financial literacy has a significant positive impact on the performance and long-term investment of UMKM. UMKMs with good financial literature are able to make better financial decisions, manage risks well, and plan their business growth well. The Government and various associated agencies have launched a number of programmes to improve financial literacy for UMKM. However, there are still some challenges in the implementation of the program, such as diverse levels of understanding, limited access to resources, and lack of supporting infrastructure. To overcome these challenges and increase the effectiveness of UMKM financial literature programmes, some of the solutions that can be applied are segmentation and customization of material, use of information technology, strengthening of infrastructure, program collaboration and synergy, and use of digital/marketplace platforms